1989
DOI: 10.1677/joe.0.1230075
|View full text |Cite
|
Sign up to set email alerts
|

Differential secretory rhythm of growth hormone controls the number of hepatic epidermal growth factor receptors in the rat

Abstract: The effect of human GH (hGH) on hepatic epidermal growth factor (EGF) receptors in the rat was investigated. Continuous administration of hGH through an osmotic minipump, mimicking the female pattern of GH secretion, to normal male rats reduced the binding of 125I-labelled EGF to hepatic membranes to the normal female levels. The same treatment of hGH applied to hypophysectomized males had no apparent effect on EGF binding. Intermittent s.c. administration of hGH twice a day (every 12 h), mimicking the male pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Since orchiectomy reduces the serum level of EGF and the content of EGF in the submandibular salivary gland in mice [2,16], this gland may be one of the sites through which androgen exerts its promoting effect on liver tumourigenesis in mice. This is supported by several studies which show that androgen increases EGF receptors in the liver [1,9,16].…”
Section: Discussionsupporting
confidence: 53%
“…Since orchiectomy reduces the serum level of EGF and the content of EGF in the submandibular salivary gland in mice [2,16], this gland may be one of the sites through which androgen exerts its promoting effect on liver tumourigenesis in mice. This is supported by several studies which show that androgen increases EGF receptors in the liver [1,9,16].…”
Section: Discussionsupporting
confidence: 53%
“…In rodents, EGFR expression is higher in males than in females as evidenced by specific binding of labeled EGF to purified liver membranes, determination of EGFR mRNA, and immunoblotting from solubilized liver (Ekberg et al 1989, Johansson et al 1989, Miquet et al 2013. Furthermore, in hypophysectomized rats of both sexes, intermittent GH treatment enhanced hepatic Egfr mRNA concentrations compared with levels for normal male rats, while continuous GH administration was less effective or did not have any effects at all (Ekberg et al 1989, Kashimata et al 1989. In contrast, other authors found no differences between intermittent and continuous administration of hGH on the induction of Egfr mRNA or EGF binding when administered to hypophysectomized male and female rats (Johansson et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…GH has been shown to modulate the expression of Egfr in the liver (Jansson et al 1988, González et al 2010. Egfr mRNA levels and EGF binding to liver were reported to be more efficiently induced by a pulsatile pattern of plasma GH concentration (Jansson et al 1988, Ekberg et al 1989, Kashimata et al 1989. However, results of these studies are controversial since other authors found no differences on the induction of Egfr mRNA or EGF binding when the hormone was administered by intermittent injections or continuous infusion to hypophysectomized rats (Johansson et al 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Transforming growth factor-(TGF-), assumed to be an important mitogen in regenerating liver (Fausto & Mead, 1989), is another possible mediator of GHstimulated liver growth. It has been reported that GH stimulates the synthesis of hepatic TGF-a/epidermal growth factor (EGF) receptors (Ekberg et al 1989;Kashimata, Hiramatsu & Minami, 1989). Moreover, the proliferative effect of EGF is enhanced in hepato¬ cytes from regenerating liver, although the number of available TGF-a/EGF receptors is decreased (Francavilla, Ove, Polimeno et al 1986).…”
Section: Resultsmentioning
confidence: 99%